Development of Sharia-based Financial: An Implementation in the Halal Food Industry - Iwan Hermawan; Gita Hindrawati; Sartono Sartono (Research Synergy Foundation, 2024)
Islamic studies in Indonesia are rapidly expanding in the financial realm. Sharia-based financial calculations are an important element in ensuring compliance with Islamic Sharia in various financial products and services affiliated with the halal food industry. The principle of sharia calculation in the halal industry includes the formulation of prohibitions such as interest (riba), gambling, fraud, and loss. As a Muslim-majority nation, Indonesia holds significant potential to lead in Islamic economics, particularly in finance. However, the management of information systems in the halal food sector remains underdeveloped, with many halal companies relying on conventional systems instead of Sharia-compliant solutions. This study seeks to address the identified issue by developing a Sharia-compliant information system for the food and beverage industry where the existing information system acquires halal, infaq, sadaqah, and waqf calculations by uploading without involving tax obligations. Data collection was conducted from halal-certified companies with branch offices in Semarang and Surakarta, while user requirements were defined through technical discussions with main managers and branch heads to ensure system relevance. Implementation of system development methods using a prototype approach by acquiring system development theory. In its contribution, feedback from users who are business people in the halal industry includes sharia after tax, displaying suppliers of products that have the legality of halal certification and product prices that are above the price of potential products: so that even though halal production costs more, the resulting information system will be able to control these costs. This system is able to reduce and control costs so that the company remains in the profit corridor.